2013
DOI: 10.1021/bi301710c
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl Phosphorylates E6AP and Regulates Its E3 Ubiquitin Ligase Activity

Abstract: In human papillomavirus (HPV)-infected cells, the p53 tumor suppressor is tightly regulated by the HPV-E6-E6AP complex, which promotes it for proteasomal degradation. We previously demonstrated that c-Abl tyrosine kinase protects p53 from HPV-E6-E6AP complex-mediated ubiquitination and degradation under stress conditions. However, the underlying mechanism was not defined. In this study, we explored the possibility that c-Abl targets E6AP and thereby protects p53. We demonstrated that c-Abl interacts with and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…We were particularly interested in Tyr 533 , which is an Angelman syndrome mutation site and which participates in a pattern of side chain interactions between subunits (75). Tyrosine 533 also exists in the region of subunit interface recently suggested by Chan et al to be sensitive to cAbl-dependent regulation by phosphorylation of Tyr 636 (76). For two of the subunits in the trimer structure, the side chain phenolic group of Tyr 533 hydrogen bonds with the amide hydrogen of Asp 543 present on the same polypeptide chain (Fig.…”
Section: A Trimer Is the Likely Fully Active Form Of E6ap-to Testmentioning
confidence: 85%
See 1 more Smart Citation
“…We were particularly interested in Tyr 533 , which is an Angelman syndrome mutation site and which participates in a pattern of side chain interactions between subunits (75). Tyrosine 533 also exists in the region of subunit interface recently suggested by Chan et al to be sensitive to cAbl-dependent regulation by phosphorylation of Tyr 636 (76). For two of the subunits in the trimer structure, the side chain phenolic group of Tyr 533 hydrogen bonds with the amide hydrogen of Asp 543 present on the same polypeptide chain (Fig.…”
Section: A Trimer Is the Likely Fully Active Form Of E6ap-to Testmentioning
confidence: 85%
“…In contrast, disrupting the hydrogen bond between Lys 688 in the small N-terminal subdomain and Glu 535 in the adjacent large N-terminal subdomain by mutation of the former has no consequence, indicating that the effects of the previous mutations are specific to those residues rather than a general feature of the interface. Interestingly, this subunit interface harbors Tyr 636 , which Chan et al (76) have identified as a substrate for c-Abl phosphorylation in the regulation of E6AP function. Chan et al (76) have speculated that the inhibition of E6AP activity observed on phosphorylation of Tyr 636 might result from blocking oligomerization of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, may promote the formation of a RSP5 trimer, analogous to the crystallographic trimer formed by the truncated E6AP construct that is lacking the α1′-helix. It should be noted, however, that the trimerization of E6AP was suggested to be associated with hyper-activation (Chan et al, 2013;Ronchi et al, 2014), whereas the proposed RSP5 trimer model confers auto-inhibition. This model of RSP5 regulation has profound structural implications, in particular for the role of the α1′-helix, but also for the adjacent N-terminal regions and intramolecular domain interactions that await to be explored.…”
Section: Rsp5: Auto-ubiquitination Oligomerization and The Exositementioning
confidence: 99%
“…Moreover, various studies have referenced the crystallographic trimer to rationalize mutational results (Chan et al, 2013;Ronchi et al, 2014;Mortensen et al, 2015;Yi et al, 2015). For instance, several mutations at the crystallographic trimer interface, including F727D, R626A, D543A, Y533A (a mutation site in Angelman syndrome), and Y636D (a variant mimicking phosphorylation of Y636 by the tyrosine kinase c-ABL) were found to reduce the activity of E6AP, nourishing the idea that the E6AP trimer represents an activated state (Chan et al, 2013;Ronchi et al, 2014). …”
Section: E6ap: To Trimerize or Not To Trimerizementioning
confidence: 99%
See 1 more Smart Citation